Lupus low disease activity state and remission and risk of mortality in patients with systemic lupus erythematosus: a prospective, multinational, longitudinal cohort study. (December 2022) - Kandane-Rathnayake, Rangi; Golder, Vera; Louthrenoo, Worawit; Chen, Yi-Hsing; Cho, Jiacai; Lateef, Aisha; Hamijoyo, Laniyati; Luo, Shue-Fen; Wu, Yeong-Jian J; Navarra, Sandra V; Zamora, Leonid; Li, Zhanguo; et al.
Summary: Background: Treat-to-target goals for patients with systemic lupus erythematosus (SLE) have been validated to protect against organ damage and to improve quality of life. We aimed to investigate the association between lupus low disease activity state (LLDAS) and remission and risk of mortality in patients with SLE. We hypothesised that LLDAS has a protective association with mortality risk. Methods: In this prospective, multinational, longitudinal cohort study, we used data from patients with SLE in the Asia Pacific Lupus Collaboration cohort collected between May 1, 2013, and Dec 31, 2020. Eligible patients were adults (aged ≥18 years) who met either the 1997 American College of Rheumatology modified classification criteria for SLE or the 2012 Systemic Lupus International Collaborating Clinics classification criteria. The primary outcome was all-cause mortality, and LLDAS, remission, and variations of remission with lower glucocorticoid thresholds were the primary exposure variables. Survival analyses were used to examine longitudinal associations between these endpoints and risk of mortality. This study is registered with ClinicalTrials.gov, NCT03138941 . Findings: Among a total of 4106 patients in the cohort, 3811 (92·8%) patients were included in the final analysis (median follow-up 2·8 years [IQR 1·0–5·3]; 3509 [92·1%] women and 302 [7·9%] men), of whom 80 died during the observation period (crude mortality rate 6·4 deaths per 1000 person-years). LLDAS was attained at least once in 43 (53·8%) of 80 participants who died and in 3035 (81·3%) of 3731 participants who were alive at the end of the study (p<0·0001); 22 (27·5%) participants who died versus 1966 (52·7%) who were alive at the end of the study attained LLDAS for at least 50% of observed time (p<0·0001). Remission was attained by 32 (40·0%) of 80 who died and in 2403 (64·4%) of 3731 participants who were alive at the end of the study (p<0·0001); 14 (17·5%) participants who died versus 1389 (37·2%) who were alive at the end of the study attained remission for at least 50% of observed time (p<0·0001). LLDAS for at least 50% of observed time (adjusted hazard ratio 0·51 [95% CI 0·31–0·85]; p=0·010) and remission for at least 50% of observed time (0·52 [0·29–0·93]; p=0·027) were associated with reduced risk of mortality. Modifying the remission glucocorticoid threshold (<5·0 mg/day prednisolone) was more protective against mortality than current remission definitions (0·31 [0·12–0·77]; p=0·012), and glucocorticoid-free remission was the most protective (0·13 [0·02–0·96]; p=0·046). Interpretation: LLDAS significantly reduced the risk of mortality in patients with SLE. Remission did not further reduce the risk of mortality compared with LLDAS, unless lower glucocorticoid thresholds were used. Funding: The Asia-Pacific Lupus Collaboration received funding from Janssen, Bristol Myers Squibb, Eli Lilly, and UCB for this study.